Diskursus Humor dan Etika dalam Perspektif Al-Qur'an - Muhamad Yoga Firdaus; Wahyudin Darmalaksana (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2021)
This study aims to discuss the ethics of humor from the perspective of the Al-Qur'an. This research method is qualitative through literature study with a social psychology approach. The results and discussion of this research include the discourse of humor and ethics and the ethics of humor from the perspective of the Al-Qur'an through social psychological analysis. This study concludes that the Al-Qur'an provides moral messages about the ethics of humor through motivation and positive emotions to produce good interactions and become guidelines for happiness in social life. This study recommends fostering a culture and humorous behavior by strengthening the ethical base of moral messages from religious texts, especially for Muslims.